Integrating WhatsApp-only Citizen Reporting and GIS Spatial Analysis (Kernel Density–Buffer–Network Distance) to Prioritize Solid Waste Service Interventions: A Case Study of Kalijaga Village, Aikmel District - Abdulah Muzakar; Isnein Akbar (International Journal of Health Engineering and Technology, 2026)
Solid waste management at the village scale faces persistent challenges related to limited availability of operational spatial data and uneven service coverage across residential areas. This study integrates WhatsApp-only citizen reporting with Geographic Information System (GIS) spatial analysis to identify clusters of solid waste complaints and to establish service intervention priorities in Kalijaga Village, Aikmel District. The spatial analysis comprises kernel density estimation, buffer analysis, and network distance analysis, while acceptance of the reporting channel is examined using an extended Technology Acceptance Model (TAM) incorporating information quality. The results indicate the formation of complaint density clusters along primary road corridors, at the interface between residential areas and vacant land, and in proximity to drainage networks. Multi-criteria integration produces priority zones P1–P5 and a Top-10 list of priority locations that can be directly adopted as a basis for task assignment and optimization of waste collection points. From the system acceptance perspective, perceived usefulness and information quality exert a significant influence on behavioral intention to use, whereas perceived ease of use affects behavioral intention indirectly through enhanced perceived usefulness. These findings demonstrate that a WhatsApp-only approach supported by GIS analysis can serve as a low-cost, operational solution for strengthening village-level solid waste governance.